Gut bacteria reflect the adaptation of Diestrammena japanica (Orthoptera: Rhaphidophoridae) to the cave - Dong, Yiyi; Chen, Qianquan; Fang, Zheng; Wu, Qingshan; Xiang, Lan; Niu, Xiaojuan; Liu, Qiuping; Tan, Leitao; Weng, Qingbei (Frontiers in Microbiology, 2022)
The gut microbiota is essential for the nutrition, growth, and adaptation of the host. Diestrammena japanica, a scavenger that provides energy to the cave ecosystem, is a keystone species in the karst cave in China. It inhabits every region of the cave, regardless of the amount of light. However, its morphology is dependent on the intensity of light. Whether the gut bacteria reflect its adaptation to the cave environment remains unknown. In this research, D. japanica was collected from the light region, weak light region, and dark region of three karst caves. The gut bacterial features of these individuals, including composition, diversity, potential metabolism function, and the co-occurrence network of their gut microbiota, were investigated based on 16S rRNA gene deep sequencing assay. The residues of amino acids in the ingluvies were also evaluated. In addition, we explored the contribution of gut bacteria to the cave adaptation of D. japanica from three various light zones. Findings showed that gut bacteria were made up of 245 operational taxonomic units (OTUs) from nine phyla, with Firmicutes being the most common phylum. Although the composition and diversity of the gut bacterial community of D. japanica were not significantly different among the three light regions, bacterial groups may serve different functions for D. japanica in differing light strengths. D. japanica has a lower rate of metabolism in cave habitats than in light regions. We infer that the majority of gut bacteria are likely engaged in nutrition and supplied D. japanica with essential amino acids. In addition, gut bacteria may play a role in adapting D. japanica’s body size. Unveiling the features of the gut bacterial community of D. japanica would shed light on exploring the roles of gut bacteria in adapting hosts to karst cave environments.